2021
DOI: 10.3389/fcell.2020.617419
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Cytolethal Distending Toxin C Exploits Lipid Rafts to Mitigate Helicobacter pylori-Induced Pathogenesis

Abstract: Helicobacter pylori infection is associated with several gastrointestinal diseases, including gastritis, peptic ulcer, and gastrointestinal adenocarcinoma. Two major cytotoxins, vacuolating cytotoxin A (VacA) and cytotoxin-associated gene A (CagA), interact closely with lipid rafts, contributing to H. pylori-associated disease progression. The Campylobacter jejuni cytolethal distending toxin consists of three subunits: CdtA, CdtB, and CdtC. Among them, CdtA and CdtC bind to membrane lipid rafts, which is cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our previous studies demonstrated that statin use significantly reduced the incidence of H. pylori -related diseases [ 41 , 44 , 45 ]. Moreover, hijacking cholesterol by antagonists competed for VacA and CagA actions via lipid rafts alleviated H. pylori -induced pathogenesis [ 46 ]. Consistent with these findings, the present study showed that depletion of cholesterol interferes with H. pylori adherence and internalization into cells, which depends on CGT.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that statin use significantly reduced the incidence of H. pylori -related diseases [ 41 , 44 , 45 ]. Moreover, hijacking cholesterol by antagonists competed for VacA and CagA actions via lipid rafts alleviated H. pylori -induced pathogenesis [ 46 ]. Consistent with these findings, the present study showed that depletion of cholesterol interferes with H. pylori adherence and internalization into cells, which depends on CGT.…”
Section: Discussionmentioning
confidence: 99%
“…CdtA/CdtC bound to the lipid rafts and cholesterol-rich microdomains within the host cell membranes [ 50 ], and there was also a report that CdtA was not essential in this process [ 51 ]. Inactivation of CdtC confirmed its role in establishing infection and ameliorates H. pylori -induced pathogenesis by hijacking cholesterol [ 52 , 53 ]. Interestingly, C. upsaliensis was reported to produce higher CDT titre than other Campylobacter [ 40 ].…”
Section: Discussionmentioning
confidence: 98%
“…AGS cells were pretreated with P. goldsteinii MTS01 (MOI = 200) followed by infection with H. pylori (MOI = 100) for 6 h. H. pylori VacA-induced cell vacuolation and CagA-induced elongated cells (hummingbird phenotype) were observed. The percentage of elongated cells was determined as reported previously ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…AGS cells were transfected with NF-κB-luciferase reporter followed by treatment with P. goldsteinii MTS01 (MOI = 200) and H. pylori (MOI = 100) for 6 h. The cell lysates were prepared and subjected to luciferase assays using Dual-Luciferase Reporter Assay System (Promega). Luciferase activity was normalized by co-transfection of β-galactosidase expression vector (Promega), as described previously ( 29 ).…”
Section: Methodsmentioning
confidence: 99%